Security, Citizenship and Human Rights - McGhee, D. author. aut Link
XI, 221 p.
Keywords: Security, Citizenship and Human Rights examines counter-terrorism, immigration, citizenship, human rights, 'equalities' and the shifting discourses of 'shared values' and human rights in contemporary Britain. The book argues that British citizenship and human rights policy is being remade and remoulded around public security and that this process could be detrimental to 'our' sense of citizenship, shared values and commitment to human rights.